PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PADA KARYAWAN PABRIK KRUPUK PULI “TELOR WALET” DUSUN KEMBANGAN DESA GARON KECAMATAN BALEREJO KABUPATEN MADIUN - Endang Rahmawati (Universitas PGRI Madiun, 2014)
This research have a purpose to study about influence of motivation work to employees productivity. Motivation represent one of factor influencing employees productivity. With existence of good motivation a employees will be responsible for the work and the work will be completed effectively and efficiently. The samples in this study using the saturated sample is all employees working in the factory pulleys crackers